Reproductive System and Genetic Diversity of Hempedu Bumi (Andrographis Paniculata) Germplasm in Peninsular Malaysia - Chia, Sok Hua (2009)
Andrographis paniculata is an erect annual plant belongs to the family of Acanthaceae. This species have been reported to possess medicinal properties such as antiviral, antithrombotic, anticancer, anti-inflammatory and many others. In spite of its significant medicinal importance, fundamental aspects regarding reproductive biology, mating system and genetic diversity of A. paniculata has been poorly investigated. The objectives of this study are to (a) determine the reproductive biology which includes the occurrence of stigma receptivity, anther dehiscence and pollen viability (b) determine the occurrence of naturally self and/or cross pollination and (c) elucidate the genetic diversity of A. paniculata germplasm in Peninsular Malaysia using molecular marker. Reproductive biology of A. paniculata was studied by investigating floral development, stigmatic receptivity, anther dehiscence and pollen viability. Two pollination treatments namely bagged and unbagged were imposed on seven accessions to study the mating system through self-compatibility and inbreeding depression. A total of 80 accessions of A. paniculata representing six different states, namely Perak, Selangor, Negeri Sembilan, Kelantan, Terengganu and Pahang were subjected to Random Amplified Polymorphic DNA (RAPD) assay using 10 primers to elucidate genetic diversity of this plant in Peninsular Malaysia. Results showed that floral development of A. paniculata can be categorised into five stages based upon flower buds length associated with timing of anther dehiscence and stigma receptivity. The anthers started to dehisce when flower buds reached the size of 11.5 mm (Stage III) and stigma became fully receptive at 12 mm (Stage IV). Both events occurred almost simultaneously when corolla still remained close. In addition, stigma of A. paniculata was closely attached to anthers from stage II until flower opening. Thereby, the mode of mating system of A. paniculata can be defined as pollination in flower bud before anthesis, also known as preanthesis cleistogamy. This mechanism of mating system greatly promotes the occurrence of autonomous self-pollination.